1978
DOI: 10.1152/jappl.1978.45.4.557
|View full text |Cite
|
Sign up to set email alerts
|

Exercise ventilation correlates positively with ventilatory chemoresponsiveness

Abstract: To determine the relationship of ventilatory responsiveness to hypoxia and hypercapnia to exercise hyperpnea, these responses and steady-state exercise ventilation (VE) were measured in 16 athletes during light (1/3 VO2 max) and heavy (2/3 VO2 max) exercise. Both the hypoxic and hypercapnic ventilatory responses correlated positively with VE per unit metabolic rate (VE/VCO2) at both exercise levels (P less than 0.05). The contribution of the hypoxic response to normoxic exercise VE was quantified by comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
52
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 0 publications
3
52
0
Order By: Relevance
“…The group-by-time interaction was tested. Because the hypoxic ventilatory response correlates to the body surface area, 2,20,21 changes in ventilation in response to hypoxia were normalized for body surface area and related to the ventilatory response to exercise (characterized by the regression slope relating ventilation to CO 2 output during exercise, V E/V CO 2 slope) through linear regression analysis. 11 Responses to hypercapnia were compared by a Mann-Whitney test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The group-by-time interaction was tested. Because the hypoxic ventilatory response correlates to the body surface area, 2,20,21 changes in ventilation in response to hypoxia were normalized for body surface area and related to the ventilatory response to exercise (characterized by the regression slope relating ventilation to CO 2 output during exercise, V E/V CO 2 slope) through linear regression analysis. 11 Responses to hypercapnia were compared by a Mann-Whitney test.…”
Section: Discussionmentioning
confidence: 99%
“…1 Peripheral chemoreceptors also play an important modulatory role in the regulation of ventilation during exercise. [2][3][4][5] This is evidenced by the observation that breathing oxygen decreases ventilation and increases arterial carbon dioxide to a greater extent during exercise than at rest. 6,7 Central chemoreceptors are located in the brain stem and respond primarily to hypercapnia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the obesity factor described above, numerous other factors Vol.32, No.4, 1982 Y. OHYABU, A. YOSHIDA, F. HAYASHI, N. SATO, and Y. HONDA have been reported to affect hypoxic sensitivity : altitude exposure (MILLEDGE and LAHIRI, 1967;WEIL et al, 1971a), athleticism (BYRNE-QUINN et al, 1971;MARTIN et al, 1978), hyperthermia (NATALINO, 1977), mixed venous PCO2, level (REBUCK and WOODLEY, 1975), malnutrition (DAEKEL, 1976), aging (KRONENBERG and DRAGE, 1973, familial or genetic factor (COLLINS et al, 1978 ;KAWAKAMI et al, 1981a ;KAWAKAMI et al, 1981b), congenital cyanotic heart disease (SORENSEN and SEVERINGHAUS, 1968 ;BLESA et al, 1977), various drugs, anesthesia or sedation (HIRSHMAN et al, 1975a ;HIRSHMAN et al, 1975b ;YACOUB et al, 1976;HIRSHMAN et al, 1977;KNILL and GELB, 1978;LAKSHMINARAYAN et al, 1978 ;SANDERS et al, 1980), and alveolar hypoventilation syndromes (SHANNON and KELLY, 1977 ;BRADLEY et al, 1979 ;SCHIFFMAN et al, 1980;BERMAN et al, 1981 ;HUNT et al, 1981). None of the above factors, however, seems to satisfactorily explain the results obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral chemosensitivity was assessed by hypoxic ventilatory responsiveness (HVR) and central chemosensitivity by hypercapnic ventilatory responsiveness (HCVR), both at rest. Since it has been reported that HVR [10][11][12] and HCVR [13] increase with increasing exercise intensity, and that the exercise estimates of HVR depend on the resting estimates of HVR [11,12,14], the individual differences in exercise estimates of chemosensitivities at varying work rates were assumed to be predicted from those in the resting estimates.…”
mentioning
confidence: 99%